2014
DOI: 10.1016/j.bbapap.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Secretome profiling of primary human skeletal muscle cells

Abstract: The skeletal muscle is a metabolically active tissue that secretes various proteins. These so-called myokines have been proposed to affect muscle physiology and to exert systemic effects on other tissues and organs. Yet, changes in the secretory profile may participate in the pathophysiology of metabolic diseases. The present study aimed at characterizing the secretome of differentiated primary human skeletal muscle cells (hSkMC) derived from healthy, adult donors combining three different mass spectrometry ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
121
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 34 publications
0
121
0
2
Order By: Relevance
“…Expression of the V3 transcript in vivo has been detected in mouse, rat, and human fetal and adult tissues and cells (46 -50), and most recently, secretion of V3 protein by primary human skeletal muscle cells was detected by proteomic analysis (51). Previous studies have shown that V3 expression induces increases in cell-cell and cell-ECM association (19,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the V3 transcript in vivo has been detected in mouse, rat, and human fetal and adult tissues and cells (46 -50), and most recently, secretion of V3 protein by primary human skeletal muscle cells was detected by proteomic analysis (51). Previous studies have shown that V3 expression induces increases in cell-cell and cell-ECM association (19,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that V3 expression induces increases in the differentiated SMC markers as well as in components of basement membrane and elastic fibers suggest that ASMCs can be reprogrammed to actively synthesize the ECM components present in healthy arteries while maintaining a differentiated and contractile phenotype. Intriguingly, proteomic profiling by mass spectrometry has identified V3 as part of the secretome of primary human skeletal muscle cells (51), suggesting it may play an intrinsic role in promoting muscle cell differentiation. FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, probably in an autocrine or paracrine fashion, myokines may regulate skeletal muscle metabolism and differentiation. Using proteomics approaches, several myokines have been identified in human myotubes [18][19][20]. Importantly, various myokines were found in secretory intercellular communicating vesicles, particularly in exosomes [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, skeletal muscle is recognised as an endocrine organ, and proteins expressed by and released from skeletal muscle have been termed myokines [1]. In three studies using primary human myotubes and proteomic approaches, hundreds of myokines have been identified, including more than 50 novel myokines [2][3][4].…”
Section: Introductionmentioning
confidence: 99%